ANALISA ABILITY TO PAY PENGGUNA JASA KERETA API SIBINUANG PADANG – PARIAMAN - Nanang Amin; Melti Roza Adry (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2018)
This study aims to determine the most ideal ticket prices in accordance with the ability to pay Sibinuang rail service users. The type of this research is descriptive analysis with quantitative approach, with sample of rail service user of Sibinuang who have entered working age. Data collection methods with questionnaires and online questionnaires to service users. Measurement of Ability To Pay (ATP) using household budget method. The result of the research is the estimated average value of ATP of IDR. 7808, -. ATP middle value IDR. 5,200, -. With 58% of respondents can be accomodated by the current ticket price (existing). For respondents Students (33%) estimated average ATP of IDR. 5.736, -. Only 42.4% are able to pay according to existing ticket prices. For pricing we should also consider the value of ATP.